Application of Registration Queue System Simulation with Multi Chanel-Multi Phase Method at Royal Prima General Hospital with Promodel - Falleryan, Muhammad; P.S, Axel Juanito; Nurcahya, Dimas; Tosida, Eneng Tita; Sugara, Victor Ilyas; Subandi, Kotim (iora, 2025)
Royal Prima General Hospital often faces the problem of patient accumulation, especially at the initial registration stage, which results in increased waiting time and decreased service quality. To overcome this problem, this study implemented a multi-channel multi-phase queuing system using Promodel simulation software. This method allows the distribution of patients into multiple lanes and service stages, thereby reducing congestion and shortening waiting times. The research data was taken from a simulation that included 500 patients in the first phase (registration) and 100 patients each in the second phase (internal medicine polyclinic) and third phase (neurology polyclinic). The simulation results show that the multi-channel multi-phase queuing system is able to handle the flow of patients effectively with an average waiting time of 1.75 minutes before receiving service. Facility utilisation rates show that the internal medicine and neurology polyclinic areas operate almost at full capacity (above 90%), while the admission area has an underutilised capacity (31.8%).